2004
DOI: 10.1128/aem.70.7.4151-4157.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substratum Surface Chemistry and Surface Energy on Attachment of Marine Bacteria and Algal Spores

Abstract: Two series of self-assembled monolayers (SAMs) of -substituted alkanethiolates on gold were used to systematically examine the effects of varying substratum surface chemistry and energy on the attachment of two model organisms of interest to the study of marine biofouling, the bacterium Cobetia marina (formerly Halomonas marina) and zoospores of the alga Ulva linza (formerly Enteromorpha linza). SAMs were formed on gold-coated glass slides from solutions containing mixtures of methyl-and carboxylic acid-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(153 citation statements)
references
References 42 publications
6
143
3
1
Order By: Relevance
“…Application of SAM in biofouling research was pioneered by the Lopez group [25,64]. Extensive studies followed, focusing on various surface properties including wettability, hydration, and lubricity [31,33,64,67,77,78]. Figure 6a shows a compiled viewgraph of Ulva linza zoospore settlement, Navicula perminuta settlement, and protein resistance on different aliphatic SAMs [64], methyl terminated oligosaccharide SAMs [48,65], and oligoethyleneglycol based SAMs with aliphatic termination [31].…”
Section: Surface Cues Can Trigger Permanent Adhesion Of Zoospores Of mentioning
confidence: 99%
“…Application of SAM in biofouling research was pioneered by the Lopez group [25,64]. Extensive studies followed, focusing on various surface properties including wettability, hydration, and lubricity [31,33,64,67,77,78]. Figure 6a shows a compiled viewgraph of Ulva linza zoospore settlement, Navicula perminuta settlement, and protein resistance on different aliphatic SAMs [64], methyl terminated oligosaccharide SAMs [48,65], and oligoethyleneglycol based SAMs with aliphatic termination [31].…”
Section: Surface Cues Can Trigger Permanent Adhesion Of Zoospores Of mentioning
confidence: 99%
“…One major advantage is that the mechanical properties are determined by the substrate while physicochemical properties, such as wetting and hydration are determined by the thin organic film. The accumulation of C. marina on chemically differently terminated self-assembled monolayers (SAMs) revealed that surface properties change the amount of accumulated biomass [14,29]. In this article we describe the effect of undecanethiol SAMs with -CH 3 , -NH 2 , -OC 7 F 10 CF 3 termination and polyethylene glycol (PEG) terminated SAMs on the adhesion strength of the marine bacteria C. marina.…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate the applicability of the microfluidic assay, we used self-assembled monolayers as welldefined model surfaces. Self-assembled monolayers [25,26] are highly useful tools to reproducibly prepare coatings and frequently applied to study response of marine biofouling organisms [14,16,[27][28][29][30][31][32]. One major advantage is that the mechanical properties are determined by the substrate while physicochemical properties, such as wetting and hydration are determined by the thin organic film.…”
Section: Introductionmentioning
confidence: 99%
“…Ulva spores were demonstrated to have a reduced tendency to settle on negatively charged surfaces of polytetrafluoroethylene (PTFE) [64]. Many other phenomena observed during microorganism settlement on self-assembled monolayers [121,144] can be partly explained by electrostatic interactions [145,146]. Discharge treatment can be used to create carboxylic acid groups on polymer surfaces [147], which can also be discussed in terms of the repulsive electrostatic interactions [148].…”
Section: Antifouling By Changing the Zeta Potentialmentioning
confidence: 99%
“…Study has shown that fouling diatoms [37] adhere more strongly to a hydrophobic polydimethylsiloxane (PDMSE) surface than to glass. For other fouling organisms such as bacteria and Ulva spores, if the surface contact angle is greater than the adhesion is stronger [121][122][123][124]. However, the strength of attachment of Ulva spores is greater to hydrophilic than hydrophobic surfaces [66,125].…”
Section: Antifouling By Modification Of Surface Topography and Hydropmentioning
confidence: 99%